Therapeutic Targeting of Proteostasis in Amyotrophic Lateral Sclerosis—a Systematic Review and Meta-Analysis of Preclinical Research - Elliott, Elizabeth; Bailey, Olivia; Waldron, Fergal M.; Hardingham, Giles E.; Chandran, Siddharthan; Gregory, Jenna M. (Frontiers in Neuroscience, 2020)
Background Amyotrophic lateral sclerosis (ALS) is a rapidly progressive fatal neurodegenerative condition. There are no effective treatments. The only globally licensed medication, that prolongs life by 2-3 months, was approved by the FDA in 1995. One reason for the absence of effective treatments is disease heterogeneity noting that ALS is clinically heterogeneous and can be considered to exist on a neuropathological spectrum with frontotemporal dementia. Despite this significant clinical heterogeneity, protein misfolding has been identified as a unifying pathological feature in these cases. Based on this shared pathophysiology, we carried out a systematic review and meta-analysis to assess the therapeutic efficacy of compounds that specifically target protein misfolding in preclinical studies of both ALS and FTD. Methods Three databases: (i) Pubmed, (ii) MEDLINE and (iii) EMBASE were searched. All studies comparing the effect of treatments targeting protein misfolding in pre-clinical ALS or FTD models to a control group were retrieved. Results Systematic review identified 70 pre-clinical studies investigating the effects of therapies targeting protein misfolding on survival. Meta-analysis revealed that targeting protein misfolding did significantly improve survival compared to untreated controls (p<0.001, (df)=68, = 0.05, (CI) 1.05-1.16), with no evidence of heterogeneity between studies (I2= 0%). Further subgroup analyses, evaluating the effect of timing of these interventions, showed that, only treating prior to symptom onset (n=33), significantly improved survival (P<0.001, df=31, = 0.05, (CI) 1.08-1.29), although this likely reflects the inadequate sample size of later time points. Furthermore, arimoclomol was found to significantly reduce secondary outcome measures including: (i) histological outcomes, (ii) behavioural outcomes and (iii) biochemical outcomes (p<0.005). Conclusions This analysis supports the hypothesis that protein misfolding plays an important role in the pathogenesis of ALS and FTD and that targeting protein misfolding, at least in pre-clinical models, can significantly improve survival, especially if such an intervention is administered prior to symptom onset.